Synergistic interactions of begomoviruses with sweet potato chlorotic stunt virus (genus Crinivirus) in sweetpotato (Ipomoea batatas L.) - Cuéllar, Wilmer Jose; Galvez, Marco; Fuentes, S.; Tugume, Joab K.; Kreuze, Jan F. (Wiley, 2015)
Three hundred and ninety‐four sweet potato accessions from Latin America and East Africa were screened by polymerase chain reaction (PCR) for the presence of begomoviruses, and 46 were found to be positive. All were symptomless in sweet potato and generated leaf curling and/or chlorosis in Ipomoea setosa. The five most divergent isolates, based on complete genome sequences, were used to study interactions with Sweet potato chlorotic stunt virus (SPCSV), known to cause synergistic diseases with other viruses. Co‐infections led to increased titres of begomoviruses and decreased titres of SPCSV in all cases, although the extent of the changes varied notably between begomovirus isolates. Symptoms of leaf curling only developed temporarily in combination with isolate StV1 and coincided with the presence of the highest begomovirus concentrations in the plant. Small interfering RNA (siRNA) sequence analysis revealed that co‐infection of SPCSV with isolate StV1 led to relatively increased siRNA targeting of the central part of the SPCSV genome and a reduction in targeting of the genomic ends, but no changes to the targeting of StV1 relative to single infection of either virus. These changes were not observed in the interaction between SPCSV and the RNA virus Sweet potato feathery mottle virus (genus Potyvirus), implying specific effects of begomoviruses on RNA silencing of SPCSV in dually infected plants. Infection in RNase3‐expressing transgenic plants showed that this protein was sufficient to mediate this synergistic interaction with DNA viruses, similar to RNA viruses, but exposed distinct effects on RNA silencing when RNase3 was expressed from its native virus, or constitutively from a transgene, despite a similar pathogenic outcome.